Secure File Sharing System in Cloud Using AES and Time Stamping Algorithms. Issue 1 (August 2020) - Sheeja, R.; Bibin, Chidambaranathan; Krishnan, Priya R; Nishanth, R.; Gopinath, S.; Ashok, K.G.
Abstract: In recent days, the growth of digital data has been increased explosively due to data-intensive applications like healthcare, education and electronic commerce. Due to the huge volume of data created and the utilization of data in emerging applications, a local storage device has to be deployed. Cloud storage services allow both the individuals and commercial users for the outsourcing of data to the cloud server and to access the data remotely with the help of the internet, so the demand for cloud storage has been raised. However, one of the critical problems of cloud data storage is security. Some researchers have used third party auditor for verifying the data stored in the cloud. This paper introduces a novel method for cloud storage and for protecting the organizations' data. The proposed system strengthens the level of authentication with the help of AES and time-stamping algorithms. The experimental results demonstrate the efficiency of the proposed method when auditing the shared data integrity